Should salvage surgery be considered for local recurrence after definitive chemoradiation in locally advanced non-small cell lung cancer? - Schreiner, Waldemar; Dudek, Wojciech; Lettmaier, Sebastian; Fietkau, Rainer; Sirbu, Horia (Journal of Cardiothoracic Surgery, 2016)
Incidence of local relapse after definitive chemoradiation (>59 Gy) for locally advanced non-small-cell lung cancer (NSCLC) is high, irrespective of high dose radiation applied. Experience with salvage lung resections in patients with locally relapsed NSCLC after definitive chemoradiation is limited. We present our series of salvage lung resections for local NSCLC relapse after curative-intent chemoradiation for locally advanced tumor.Nine consecutive patients with local tumor recurrence or persistence following definitive chemoradiation were reviewed. Kaplan-Meier analysis was used to assess patient survival.All patients received definitive radiation (median dose 66.2 Gy) with concurrent chemotherapy. Tumor stage prior to chemoradiation was IIIA in 8 patients and IV in 1. In 4 patients tumor invaded the chest wall, in 2 the spine and in 1 the aorta. Median interval between chemoradiation and salvage resection was 30.2 weeks. Nine patients underwent 9 resections (6 lobectomies, 1 bilobectomy, 1 pneumonectomy and 1 bi-segmentectomy). One death occurred on the 12th postoperative day. Median overall survival was 23 months; postoperative 3-year survival was 47 %. Median progression-free survival was 21 months.Salvage lung resection for locally recurrent or persisted NSCLC in selected patients with locally advanced NSCLC following definitive chemoradiation is a worthwhile treatment option.
EVALuna2:18249